The influence of social media communication on consumer's attitudes and behavioral intentions concerning brand-sponsored events - Schivinsky, B; Langaro, D.; Shaw, C. (Event Management, 2019)
Social media communication was suggested to influence consumers on their decision process of participating in events. Despite the relevance of evaluating this proposition, the effects of social media brand-related communications on event attendance were not yet validated. In order to address this literature gap, it was evaluated whether firm-created and user-generated social media brand-related content influenced consumers’ attitudes and, consequently, their intentions to participate in brand-sponsored events. Additionally, the mediating role of consumers’ attitudes towards the brand and the event was examined. An online survey (n=307) was implemented and results were analyzed with structural equation modeling (SEM). The findings contribute to managers and scholars in the field of events marketing in general and brand-sponsored events in specific, by means of proposing and validating a model that confirms (i) the effects of firm-created SM brand-related content on brand attitude, (ii) the influence of user-generated SM brand-related content on both brand and event attitudes, (iii) the impact of brand attitude on event attitude, (iv) the influence of event attitude on the consumers’ intentions to participate; and identifies (v) different arrays revealing how consumers’ attitudes towards the brand and the event mediate the relationship between SM communications on consumers’ behavioral intentions, whilst distinguishing the type of SM brand-related content source.